The Physics of Sunlight and Cells - Sabzalian , M (Elsevier, 2024)
This chapter aims to explain the physics of sunlight, cells and their structure, and the conversion of sunlight into electricity. This section will be mainly theoretical and specialized and present the equations related to this phenomenon. . The main content includes properties of sunlight, fundamentals of a solar cell, basic semiconductor physics, and Concentrated semiconductors. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.
Keywords: concentrated semiconductors; principles of a solar cell; Properties of sunlight; semiconductor physics